Tinjauan Maqashid Syariah terhadap Halal Life Style Busana Bermotif Kalimat Thayyibah pada Remaja di Kota Bandung - Yovanka Graciela; Nandang Ihwanudin; Neng Dewi Himayasari (Bandung Conference Series: Sharia Economic Law, 2022)
Abstract. Maqashid Syariah aims to uphold the benefit of humans as social beings, in which he must be responsible for himself later on to Allah, as is the case in modern times there is the use of fashion styles with the thayyibah sentence motif or sellers who sell thayyibah-patterned clothing. As it is known that the thayyibah sentence is a holy sentence and a good sentence. This study aims to determine how consumer behavior and how the sharia maqashid review of the halal life style of clothing patterned with thayyibah sentences in teenagers in the city of Bandung. This research method uses descriptive qualitative with the type of field research data and data taken based on the results of observations, and interviews with consumers or buyers of clothing patterned with thayyibah sentences, clothing sellers with thayyibah sentences, religious leaders who understand the law wearing clothes with thayyibah motifs, and lecturers. Faculty of Sharia, Islamic University of Bandung. Regarding the results of this study, there are 2 opinions that allow and do not allow wearing or selling clothes with the pattern of thayyibah sentences. Abstrak. Maqashid Syariah bertujuan untuk menegakkan kemaslahatan manusia sebagai makhluk sosial, yang mana ia harus bertanggung jawab atas dirinya sendiri nanti pada Allah, sebagaimana yang terjadi di zaman yang modern ini terdapat pemakaian style busana bermotif kalimat thayyibah ataupun para penjual yang menjual busana bermotif kalimat thayyibah. Seperti yang diketahui bahwa kalimat thayyibah itu kalimat yang suci dan kalimat yang baik. Penelitian ini bertujuan untuk mengetahui bagaimana perilaku konsumen dan bagaimana tinjauan maqashid syariah terhadap halal life style busana bermotif kalimat thayyibah pada remaja dikota bandung. Metode penelitian ini menggunakan kualitatif deskriptif dengan jenis data field research dan data yang diambil berdasarkan hasil observasi, dan wawancara dengan pihak kosumen atau pembeli busana bermotif kalimat thayyibah, penjual busana bermotif kalimat thayyibah, tokoh agama yang memahami hukum memakai busana bermotif kalimat thayyibah, dan Dosen Fakultas Syariah Universitas Islam Bandung. Terkait hasil penelitian ini ada ada 2 pendapat yang memperbolehkan dan tidak memperbolehkan memakai atau menjual busana bermotif kalimat thayyibah.